Analysis of the correlation between the variables determining competition performance in cross-country skiing - Pustovrh, Janez (Kinesiologia Slovenica, 2005)
An analysis of some of the potential criteria of a competitive performance was made on a sample of young cross-country skiers aged between 13 and 14 years. The analysis covered all six races of the Žito Cup and three conventionally defined criteria of a competitive performance: FIS points, the POZ criterion (average time behind the winner in % in all races of the cup series) and the K-1 criterion. By applying Hotelling's method of principal components and the Kaiser-Guttman criterion we extracted the first principal component (vector K-1) from six races of the Žito Cup, with which we succeededin explaining 83% of the variance of young cross-country skiers' performances.In this case the variable Race5, denoting the fifth race, contributed the least to the total subject of measurement. The results of the correlation analysis show a high correlation (r=0.99) between individual conventionally defined criteria of a competitive performance (FIS, POY and K-1). The lowest correlation with the remaining variables was recorded in the variable Race5, which shows that coincidental factors had quite a strong impact on this race. The correlations between the variables also show that the competitive performance of the measured subjects is not highly correlated with the cross-country skiing technique. Owing to the methodological advantages established, the application of the FIS-points variable was confirmed as a priority criterion of competition performance in both professional work in practice and in scientific research work.
Keywords: analize; kriteriji; smučarski tek; tekmovalna uspešnost